Cyclical Behavior of Public and Private Sector Banks: A Comparative Study of Non-performing Assets - Durafe, Aniruddha; Singh, Manmeet (Journal of Business and Management Research, 2016)
This study examines the cyclical behavior of both the public and private sector banks in India with a focus on non-performing assets. The motivation behind this study is to find out whether non-performing assets of public sector banks and private sector banks in India exhibit procyclical behavior. Pearson correlation coefficient results suggest countercyclical behavior of gross non-performing assets and current state of economy in both public and private sector banks. The study also employed multiple regression analysis which shows that all bank specific variables have significant effect on gross non-performing assets in public sector banks while macroeconomic variables are found to be insignificant in presence of bank specific variables. In case of private sector banks, current state of economy is found to be significant in presence of bank specific variables with negative sign. In another model, which includes only macroeconomic variables, economy wide fluctuations and inflation are found significant in both public and private sector banks in India.Journal of Business and Management Studies Vol.1(1) 2016: 14-25